Preparation and characterization of polyaniline microcapsule loaded with 2, 2′‐azobis(2‐methylpropionitrile) initiator and its controlled release. Issue 6 (31st August 2021) - Zhang, Qifan; Zuo, Mingming; Wang, Yu; Liu, Weiwei; Zuo, Xiaobing
Abstract: The thermal curing of acrylate adhesive consisting of acrylate monomer or prepolymer and 2, 2′‐azobis(2‐methylpropionitrile) (AIBN) initiator is quite common. However, the two‐component adhesive is not suitable for large areas, large gap bonding, or potting because of its fast‐curing speed and intense heat release. To solve these problems, microencapsulating the initiator AIBN in the adhesive and controlling its release is proposed. Here, a new series of polyaniline microcapsules loaded with AIBN for the preparation of delayed‐release initiator were synthesized via an emulsification‐polymerization method. The coumarone indene resins were doped in polyaniline to control the release of the encapsulated AIBN. The characterization results indicate that the coumarone indene resin had been successfully mixed into the microcapsule polyaniline shell, and the interior of the microcapsules doped with resin had a rich pore structure. When a Span 80 and Tween 80 composite emulsifying system was used and its concentration was controlled at 0.1%–1.0%, the resulting microcapsules were homogeneous with good dispersibility. The release of the microcapsule was slow, and the release rate and release time could be precisely controlled by adjusting the type and doping amount of coumarone indene resin in the microcapsule shell material as well as the external temperature. For example, when the doping amount of coumarone indene resins in the PANI shell material increased from 0.2 to 1.0 g or when the temperature ranges from 75to 85°C, the release time of AIBN from the microcapsule decreased from 9 to 2 h and 12 to 3 h, respectively. With increasing demands for high performance delayed‐release initiators, the prepared polyaniline microcapsules loaded with AIBN show great potential for practical applications in adhesive, self‐healing coating, and petroleum exploitation. Abstract :